2006
DOI: 10.1063/1.2172412
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal micromirrors for microsystems and atom chips

Abstract: Concave pyramids are created in the ͑100͒ surface of a silicon wafer by anisotropic etching in potassium hydroxide. High quality micromirrors are then formed by sputtering gold onto the smooth silicon ͑111͒ faces of the pyramids. These mirrors show great promise as high quality optical devices suitable for integration into micro-optoelectromechanical systems and atom chips. We have shown that structures of this shape can be used to laser-cool and hold atoms in a magneto-optical trap.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 16 publications
1
54
0
Order By: Relevance
“…The optical properties of such a pyramid have already been investigated in [14]. In those experiments, it was observed that light reflected near the diagonal edges can prevent the MOT from working.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…The optical properties of such a pyramid have already been investigated in [14]. In those experiments, it was observed that light reflected near the diagonal edges can prevent the MOT from working.…”
Section: Introductionmentioning
confidence: 97%
“…Atoms were successfully trapped once the gold was removed from the areas where the type-2 and type-3 rays are produced. We were also able to make the MOT operate [14] by using a lower reflectivity (78%) coating of aluminum, which was not cut away at the edges and center. In such a pyramid, the intensity of the harmful type-3 light is decreased relative to the type-1 beams, considering the additional reflection by the lossy surfaces.…”
Section: Principle Of the Mot On A Chipmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter two are attractive as they need only a single incident beam, and both are suitable for microfabrication. Miniaturized pyramid MOTs, however, suffer from low atom capture rates due to the small volume in which the beams overlap 45,46 , significant backscatter making the atoms difficult to detect 47 , and the geometry making transfer of the atoms to magnetic surface traps non-trivial. A recently demonstrated ver- sion of the tetrahedral-MOT using a planar grating as a reflector (which we refer to as the 'G-MOT', see Figure 2) can capture a large number of atoms, has lower backscatter 48 , and can be easily integrated with atom chip structures 49 .…”
Section: The Magneto Optical Trap Systemmentioning
confidence: 99%